Crisis at the WTO Is the Blocking of Appointments to the WTO Appellate Body by the United States Legally Justified? - Lehne, Jens (sui generis, 2019)
Since 2017, the United States has blocked all appointments to the Appellate Body of the World Trade Organization (WTO), thereby threatening to destroy the WTO's dispute settlement system, one of the most active dispute settlement systems in international law and a central pillar of the multilateral trading system. The United States justifies its blockage with allegations of judicial overreach, claiming that the Appellate Body in its jurisprudence has not complied with the WTO treaties.